Світильники середньовіччя - Маркович, М. (Інститут народознавства НАН України, 2008)
Among lighting devices ponderable seat is taken by the lamps of dark ages. Among them new types of lighting devices are oily lamps and candlesticks, lampadci with the monogram of Hrista. Metallic temple lamps, and then glass oily lamps, developed afterwards.